Control de evasión tributaria y sostenibilidad económica en personas con negocio en el mercado Colonial Center, Bellavista, Callao, Perú, 2022 - Laguna Silva, Alejandro (2024)
The research entitled "Control of tax evasion and economic sustainability in people with business in the Colonial Center Bellavista - Callao 2022 market", considered as an objective to establish the correspondence between tax evasion control and economic sustainability in a product market. The research was applied, quantitative and correlational. The population was made up of people with businesses from the Colonial Center Bellavista - Callao 2022 market. The technique used was the survey, and the instrument used to collect the data was the questionnaire. This instrument made it possible to determine the validity of the instrument, through the judgment of experts, and for this purpose, Cronbach's Alpha Coefficient was used in the tax evasion control questionnaire and in the economic sustainability questionnaire. The results conclude that there is a moderate positive relationship (α=.784) between tax evasion control and economic sustainability in people with business in the Colonial Center Bellavista - Callao 2022 market. However, there is a clear dissatisfaction with the application of the rules towards users. 92.0% of respondents consider that they are dissatisfied with the knowledge provided by the government about the tax system.